Cosmology and astrophysics from relaxed galaxy clusters: I. sample selection - Mantz, Adam B.; Allen, Steven W.; Morris, R. Glenn; Schmidt, Robert W.; von der Linden, Anja; Urban, Ondrej (Monthly notices of the Royal Astronomical Society, 2015)
Abstract. This is the first in a series of papers studying the astrophysics and cosmology of massive, dynamically relaxed galaxy clusters. Here we present a ne